Anxiety and perceptual-motor performance: toward an integrated model of concepts, mechanisms, and processes - Nieuwenhuys, Arne; Oudejans, Raôul R. D. (Psychological research, 2012)
Under anxiety, people sometimes perform poorly. This concerns cognitive performance (e.g., taking an important exam) as well as perceptual-motor performance (e.g., picking up a cup from a table). There is still much debate about how anxiety affects perceptual-motor performance. In the current paper we review the experimental literature on anxiety and perceptual-motor performance, thereby focusing on how anxiety affects the perception, selection, and realization of action possibilities. Based on this review we discuss the merits of two opposing theoretical explanations and build on existing frameworks of anxiety and cognitive performance to develop an integrated model that explains the various ways in which anxiety may specifically affect perceptual-motor performance. This model distinguishes between positive and negative effects of anxiety and, moving beyond previous approaches, recognizes three operational levels (i.e., attentional, interpretational, and behavioral) at which anxiety may affect different aspects of goal-directed action. Finally, predictions are formulated and directions for future research suggested.